Identification of chromosomal aberrations in a Costa Rican children population with idiopathicintellectual disability - Abarca Ramírez, Melissa (2021)
The prevalence of intellectual disability (ID) in the global population is 3%. One of the most frequent cause of ID are chromosome aberrations, which are easily detected by a karyotype. However, many of these maygoundetected during a conventional cytogenetic analysis because of their length.These small alterations can be localized in the subtelomeres and it has been observed that when localized there, they are an important cause of ID in patients without a causality diagnostic. In this observational study, we use the MLPA technique for the purpose of identifying the frequency of submicroscopicsubtelomere chromosomal aberrations in a population of people with ID of unknown origin. 70 samples were successfully analyzed with MLPA and we found one case with a microduplication in the 17p subtelomere for a frequency of 1,4%. Also,the karyotype was performed in 33cases, and we foundone case with a chromosome aberration that can be detect by microscope for a frequency of 3%. The subtelomeric chromosome aberration frequency was lower than expected as we compare our results with similar studies. Finally, with this work we conclude that the karyotype and the MLPA technique complement each other for approaching people with ID of unknown origin.